Meningoencephalitis from SARS-CoV-2 infection. (2020) - Hafizi, Fatima; Kherani, Saleema; Shams, Madeeha
Highlights: SARS-CoV-2 meningoencephalitis should be considered in patients presenting with neurologic symptoms during this pandemic. Patients with high suspicion for SARS-CoV-2 neurologic involvement should receive brain imaging and lumbar puncture. A verified assay for detecting SARS-CoV-2 virus RNA in cerebrospinal fluid needs development for acute care center use. Abstract: The current global pandemic of COVID-19 disease is caused by a novel coronavirus SARS-CoV-2. This typically causes severe respiratory illness, however, as cases have multiplied across the globe, protean manifestations involving multiple organ systems have been described. We report a case of a 35-year-old woman with meningoencephalitis associated with COVID-19 disease who presented with altered mental status and rhythmic limb movements. Although rare, meningoencephalitis should be considered as a possible manifestation of COVID-19 disease.